CHARACTERISTICS OF EFFECTIVE VOCATIONAL EDUCATION IN THE INDUSTRIAL REVOLUTION 4.0. - Irwanto Irwanto (VANOS Journal of Mechanical Engineering Education, 2019)
Effective vocational education is a dream for students, especially the community and parties involved in vocational education. Vocational schools are required to graduate their students according to what is needed by the industry in the field. Vocational education is expected to collaborate with industry to jointly develop or develop curriculum so that there is no deviation between the SMK and the industry. The purpose of this study is to find effective and efficient vocational education indicators. The research method used is a qualitative research with a descriptive approach. The results of the study found in the characteristics of effective SMKs that are the basis for developing school performance indicators can be grouped into six aspects, namely: (1) Program for improving vocational student achievement; (2) Practice learning both theory and practice; (3) School leadership; (4) Staff development and development; (5) Environmental conditions and academic climate in SMK; and (6) The participation of parents in the administration of education. SMK Negeri 2 Kotif Palopo is one of the vocational schools in the field of technology that is professional in graduating students. In this case, the graduates of SMK Negeri 2 Kotif Palopo have been scattered everywhere, especially in local industries and large industries in Indonesia, especially in Makassar City and North Sulawesi.